Optical Refractive Index Sensors with Plasmonic and Photonic Structures: Promising and Inconvenient Truth. Issue 9 (18th February 2019) - Xu, Yi; Bai, Ping; Zhou, Xiaodong; Akimov, Yuriy; Png, Ching Eng; Ang, Lay‐Kee; Knoll, Wolfgang; Wu, Lin
Abstract: Optical sensors are widely used for refractive index measurement in chemical, biomedical, and food processing industries. Due to specific field distribution of the resonances, optical sensors provide high sensitivity to ambient refractive index variations. The sensitivity of an optical sensor is highly dependent on material and structure of the sensor. Here, six major categories of optical refractive index sensors using plasmonic and photonic structures are reviewed: i) metal‐based propagating plasmonic eigenwave structures, ii) metal‐based localized plasmonic eigenmode structures, iii) dielectric‐based propagating photonic eigenwave structures, iv) dielectric‐based localized photonic eigenmode structures, v) advanced hybrid structures, and vi) 2D material integrated structures. Representative configurations working in the wavelength range of 400–2000 nm will be selected and compared in terms of bulk refractive index sensitivities, figures of merit, and working wavelengths. A technology map is established in order to define the standard and development trend for optical refractive index sensors. Abstract : Optical sensors are widely used for refractive index measurement in chemical, biomedical, and food processing industries. This article reviews six categories of optical refractive index sensors with plasmonic and photonic structures, in terms of bulk refractive index sensitivities, figures of merit, and working wavelengths. A technology map is established to define the standard and development trends.